PRAKTEK GADAI TANAH PERTANIAN DI DESA BANYUADEM, KECAMATAN SRUMBUNG, KABUPATEN MAGELANG PASCA BERLAKUNYA PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG NO 56 TAHUN 1960 - -, Yusuf (Widya Wacana: Jurnal Ilmiah, 2014)
Pawn practice paddy Agricultural Land in terms of government regulation in lieu of law No. 56 of 19 60 in the village Banyuadem, Srumbung, Magelang, showed symptoms still exist signs of life and the develop ment of such practices, although there has been prohibited by the Regulations. Pawn defined as economic activity in the form of loan guarantees. In the community, i ncluding the farming community, in the form of loan guarantees could land certificates, goods, and so on. When urgency, land can be used as collateral to secure loans pertanianpun given to the lien holders, notwithstanding,  the agricultural land is one of the means of life support the household. This study aims to determine why landowners paddy farming in the village  Banyuadem, willing to give up his farm in the form of plantations pondoh as a guarantee of the debt on the lien holder. Meanwhile, tragically, despite the Government Regulation in Lieu of Law No. 56 of 1960, already 54 years was made, the villagers Banyuadem, Srumbung, Magelang, do not know about the existence of the regulation. The research method is qualitative deskritifptif. This study describes the implementation lien  only farm in rural communities Banyuadem, Srumbung, Magelang, then analyzed based on the provisions of the agrarian law. Respondents pawn actors farmland. Data taken with the interview method. Data was analyzed qualitatively, with the deduction using the method of deductive and inductive thinking. The results of research in the village Banyuadem, Srumbung, Kabuapaten Magelang, shows that the practice of lien farmland, gardens form pondoh still ongoing in the community, even those who served as a desapun officers involved as the practice of lien.  Pawn  farmland pondoh garden is an alternative to earn money in an urgent situation. About the repayment  period is determined by the ability of the lien pledgor to redeem his land back, although the government has banned through Government Regulation in Lieu of Law No.56 of 1960. Based on the above results, it is suggested that the Government Regulation in Lieu of Law No. 56 of 1960, especially chapter 7, can run in the community, then the rules should be introduced to the village and the villagers, so that the regulation can be effective. Keywords: Pawn, Pawn paddy Land Agriculture, Government Regulation substitute Act No. 56 of 1960